Cassiterite deposition induced by cooling of a single-phase magmatic fluid: Evidence from SEM-CL and fluid inclusion LA-ICP-MS analysis. (1st February 2023) - Han, Liang; Pan, Jun-Yi; Ni, Pei; Chen, Hui
Abstract: Cassiterite (SnO2 ), the principal ore mineral of tin, is mainly formed in granite-related magmatic hydrothermal systems. The precipitation mechanism of this mineral in hydrothermal veins is still debated due to lack of direct constraints on this specific mineralization process. Here, we present a detailed reconstruction of fluid evolution history from a high-grade cassiterite-quartz vein in the Weilasituo Sn-polymetallic deposit, North China, based on combined SEM-CL imaging with fluid inclusion microthermometry, Raman and LA-ICP-MS analysis of intergrown cassiterite and gangue minerals. Formation of the cassiterite-quartz vein at Weilasituo started from early topazization and muscovite deposition along vein walls and was followed by crystallization of topaz, quartz (Q1) and cassiterite in a general sequential order. Cassiterite deposition occurred within a restricted time period before complete crystallization of topaz and quartz. Shortly after cassiterite precipitation, the vein was fractured and overprinted by later quartz generations (Q2 & Q3) and fluorite. In situ microanalysis on primary and/or pseudosecondary fluid inclusions from the different crystallization stages indicates that an acid and reduced single-phase magmatic fluid of gradually dropping temperature but very consistent salinity was responsible for vein formation. Mixing of this magmatic fluid with a biotite-plagioclase gneiss buffered, deep-cycled underground water of lower temperature and salinity occurred at the final stage, but it is not related to Sn mineralization. The physical and chemical changes of fluids bracketing cassiterite deposition demonstrate that cassiterite precipitation at Weilasituo was predominately induced by the cooling of the hydrothermal fluid by at least 50 °C, and it is accompanied by the oxidation of Sn(II)-Cl complexes with CO2 and/or As(III) species as potential oxidants. Early stage fluid-rock interaction with feldspathic host rocks and the formation of muscovite coverage on the vein walls are perhaps important for providing a fluid-buffered environment ideal for such mechanism. However, our result argues against meteoric water mixing or fluid boiling being the triggers of cassiterite deposition, and this conclusion has been further supported by cassiterite oxygen isotope analysis on the same set of samples. Additionally, the maximum base metal endowment (Pb and Zn) calculated from initial metal contents of the premineralization fluid at the Weilasituo Sn-polymetallic deposit are far less than proven reserves found in the two adjacent base metal deposits, and therefore a genetic link between these deposits is not suggested. This finding may have important implications for the ongoing exploration in the ore district.